Antioxidant activity of ethanol extract and ethyl acetate fraction of blue pea flower (Clitoria ternatea L.) - Suhesti, Tuti Sri; Rahmahwati, Devita Sukma; Warsinah, Warsinah; Nuryanti, Nuryanti; Utami, Vitis Vini Vera Ratna (Acta Pharmaciae Indonesia, 2024)
Background: The imbalance of free radicals can be mitigated by antioxidants. Natural sources, such as the blue pea flower (Clitoria ternatea L.), have gained attention as potential antioxidant alternatives. Objective: This study aimed to evaluate the antioxidant potential of the blue pea flower by extracting its fractions using n-hexane and ethyl acetate. Methods: The study employed an experimental design involving maceration for extraction, followed by fractionation using n-hexane and ethyl acetate solvents. Antioxidant activity was assessed using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. Data from both qualitative identification and antioxidant tests were analyzed descriptively and quantitatively to determine the IC50 values. Results: The analysis revealed that both the extracts and fractions of the blue pea flower contain bioactive compounds with antioxidant potential, including flavonoids, tannins, steroids, and terpenoids. The IC50 values for antioxidant activity were as follows: n-hexane fraction, 85.28 µg/mL; ethyl acetate fraction, 82.94 µg/mL; and ethanol fraction, 78.78 µg/mL. Conclusion: Flavonoids, steroids, and terpenoids were identified in both the blue pea flower extract and ethyl acetate fraction, while tannins were present only in the ethanol extract. Strong antioxidant activity was observed in all fractions, including the ethanol extract, n-hexane, and ethyl acetate fractions.